Daily insulin doses and injection frequencies of neutral protamine hagedorn (NPH) insulin, insulin detemir and insulin glargine in type 1 and type 2 diabetes: a multicenter analysis of 51 964 patients from the German/Austrian DPV‐wiss database. Issue 5 (July 2014) - Laubner, K.; Molz, K.; Kerner, W.; Karges, W.; Lang, W.; Dapp, A.; Schütt, M.; Best, F.; Seufert, J.; Holl, R. W.
Abstract Background We performed a comparative analysis of the use of long‐acting insulin (analogues) neutral protamine hagedorn (NPH), detemir (Det) and glargine (Gla), and quantified injection frequencies and daily insulin doses in patients with type 1 and 2 diabetes in daily practice. Methods A total number of 51 964 patients from 336 centres in Germany and Austria with type 1 and 2 diabetes with exclusive insulin therapy were retrospectively analysed. Results A total number of 42.1%/75.9% (type 1/type 2) of patients used NPH, 19.9%/6.7% Det and 38.0%/17.4% Gla, with similar glycaemic control and proportion of severe hypoglycaemia for NPH/Det/Gla in type 1 (Mean HbA1c 7.98%/7.98%/8.07%; mean proportion of severe hypoglycaemia 11.06%/11.93%/10.86%) and type 2 diabetes (Mean HbA1c 7.61%/7.78%/7.61%; mean proportion of severe hypoglycaemia 5.66%/4.48%/5.03%). In type 1 diabetes, the mean daily injection frequencies of NPH versus Det versus Gla were 1.9 vs 1.8 vs 1.1, and total daily insulin injections were 5.3 vs 5.6 vs 5.0. The adjusted mean daily basal insulin doses were 0.36, 0.39 and 0.31 IU/kg, mean daily total insulin dose was lowest for Gla (0.74IU/kg), followed by NPH (0.76IU/kg) and Det (0.81IU/kg). In type 2 diabetes patients, mean daily injection frequencies were 1.6 for NPH, 1.4 for Det and 1.1 for Gla, total daily insulin injections were 4.0 vs 4.1 vs 3.6. The mean daily basal insulin dosages were 0.30IU/kg (NPH), 0.33IU/kg (Det) and 0.29IU/kg (Gla), mean total insulin doses per day were 0.63IU/kg (NPH), 0.77IU/kg (Det) and 0.67IU/kg (Gla). Conclusions In a 'real‐world' setting, the injection frequencies and doses of basal and total insulin per day are lowest with the use of insulin glargine compared with NPH‐insulin or insulin detemir at similar glycaemic control and rates of severe hypoglycaemia. Copyright © 2013 John Wiley & Sons, Ltd.